Transição de fase estrutural no multiferroico KBiFe2O5 - Lima, Pedro Henrique Moreira (2019)
In this work we investigated the structural and vibrational properties of KBiFe2O5 (KBFO) ceramics by means of Raman spectroscopy and X-ray diffraction techniques under variation of hydrostatic pressure. A total of 19 active Raman modes were observed under normal conditions of temperature and pressure, which were classified based on compounds of the same structural family or having similar molecular groups. Analysis of the Raman spectra under pressure showed that the material exhibits a first order phase transition displaying a hysteresis when subjected to an increase and then to a reduction of its pressure. We used X-ray diffraction by varying the hydrostatic pressure in order to analyze the phase transition seen by Raman spectroscopy. The transition occurs in the material when it reaches around 3,45 GPa when we increase the hydrostatic pressure. The joint analysis of X-ray diffraction and Raman spectroscopy indicates that possibly the symmetry for the high pressure phase belongs to the space group Pmmm.